Intraoperative Boost Radiotherapy during Targeted Oncoplastic Breast Surgery: Overview and Single Center Experiences. (17th December 2014) - Malter, Wolfram; Kirn, Verena; Richters, Lisa; Fridrich, Claudius; Markiefka, Birgid; Bongartz, Rudolf; Semrau, Robert; Mallmann, Peter; Kraemer, Stefan
Abstract : Breast-conserving surgery followed by whole-breast irradiation is the standard local therapy for early breast cancer. The international discussion of reduced importance of wider tumor-free resection margins than "tumor not touching ink" leads to the development of five principles in targeted oncoplastic breast surgery. IORT improves local recurrence risk and diminishes toxicity since there is less irradiation of healthy tissue. Intraoperative radiotherapy (IORT) can be delivered in two settings: an IORT boost followed by a conventional regimen of external beam radiotherapy or a single IORT dose. The data from TARGIT-A and ELIOT reinforce the conviction that intraoperative radiotherapy during breast-conserving surgery is a reliable alternative to conventional postoperative fractionated irradiation, but only in a carefully selected population at low risk of local recurrence. We describe our experiences with IORT boost (50 kV energy X-rays; 20 Gy) in combination with targeted oncoplastic breast surgery in a routine clinical setting. Our experiences demonstrate the applicability and reliability of combining IORT boost with targeted oncoplastic breast surgery in breast-conserving therapy of early breast cancer.